KUALITAS PENYALURAN BANTUAN DANA PROGRAM INDONESIA PINTAR DI KOTA PEKANBARU - Putri, Diana Marisa; Sadad, Abdul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research is the result of a study that describes the quality of aid of the smart indonesia program funding in Pekanbaru City. In the implementation of the Smart Indonesia Program in Pekanbaru, problems were still found in the funds of financial aid felt by the community. The problem that still felt by the community is slow disbursement of the smart indonesia program funds, incompability of benefits of the smart Indonesia program funds, inaccurate data on the student receiving of the smar indonesia program. The purpose of the study was to find out and analyze the quality of Aid of the smart indonesian funds in pekanbaru city and find out the factors that hinder the quality of aid of funds for the Smart Indonesia Program in Pekanbaru City. The research method used is descriptive qualitative research method using informants as the object of information being studied. By using the snowball sampling method, a technique for determining the sample, which is initially small and then enlarged. The data used are primary data in the form of interviews and observations regarding the quality of aid of the Smart Indonesia program in Pekanbaru City. And secondary data, namely ministerial regulations, Number of Drop Out Students at Elementary and Middle School Levels in Pekanbaru City in 2018, Number of Students and Number of Recipients of Smart Indonesia Program at Elementary and Junior High School Level in Pekanbaru City in 2017, Recapitulation of the Number of Recipients of the Smart Indonesia Program at the Tenayan Raya District of State Junior High School in 2017, Recapitulation of the Management Education Unit of the Smart Indonesia Program in 31 State Junior High School in Tenayan Raya District in 2017. This study uses the theory of Fandy Tjiptono about quality starts from indicators of conformity with the requirements, suitability for usege, continuous improvement, free from damage, fulfillment of customer needs, do everything right, something that can make customers happy. The quality of aid of the Smart Indonesia Program in Pekanbaru City is generally not optimal. Factors that hinder the quality of aid of the smart Indonesian programs in Pekanbaru are lack of coordination, absence of socialization, and the disbursement process is not on time.Kata kunci : Quality, Aid, Program